PELATIHAN DAN PENDAMPINGAN PEMASARAN DIGITAL PADA UMKM RENGGINANG: DESAIN, IMPLEMENTASI, DAN CAPAIAN AWAL - Kamaroellah, R. Agoes; Aulia, Anis; Syafa, Wirdana; M.P, Arisandi Romadhona; Jibran H, Bakti Reynal; Fahmy, Muhammad Ali; Oktaviana, Ade Malyka Alya; Nikmah, Qurrotul Aini; Norhaliza, Siti; Ma’rufah, Siti; Afriyani, Feni Nur; Halimiyah, Eny; Sirul, Mohammad; Ali, Bahrul (Universitas Mataram, 2025)
MSMEs are small businesses owned and managed by individuals or groups with certain wealth and income limits, playing an important role in the community economy, including in Lebbek Village, Pakong District. This study used a qualitative and descriptive approach to understand the dynamics of rengginang businesses, which are local MSMEs with great potential but facing marketing constraints. Community service is focused on training in using digital technology as a marketing medium through platforms such as TikTok, Instagram, and Shopee, involving three active rengginang business actors as participants. The increase in participants’ knowledge was measured qualitatively through interviews and observations, covering their understanding of social media utilization and digital marketing strategies. However, it was not supplemented with quantitative data, such as sales or market reach changes, before and after the training. The research results show an increase in the knowledge of MSME actors in managing digital marketing and opening opportunities to expand the market. Thus, this activity not only strengthens the competitiveness of local MSMEs but also encourages rural economic development through sustainable marketing innovation.